2015
DOI: 10.5354/0719-1472.2014.36273
|View full text |Cite
|
Sign up to set email alerts
|

La paleodieta de cinco especies de mamíferos herbívoros rancholabreanos de valsequillo (Puebla, México)

Abstract: Usando las relaciones isotópicas de 13 C/ 12 C y 18 O/ 16 O presentes en el esmalte y la osteodentina, se infirió la dieta y el ambiente en el cual vivieron cinco especies extintas de herbívoros procedentes del Pleistoceno Tardío deValsequillo, Puebla, México. Los caballos, los mamutes y el perezoso mostraban una dieta basada exclusivamente en plantas C 4 , mientras que el carpincho y los gonfoterios exhibían una dieta mixta C 3 /C 4. El tipo de vegetación en el cual estos animales habitaron fue abierto con po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…These two proposed dietary behaviors indirectly indicates the presence of forested and opened vegetation areas at the Valsequillo Basin during the late Pleistocene. Perez-Crespo et al (2014) have considered a similar scenario at the Valsequillo Basin, based on data derived from the analysis of stable carbon isotopes in the teeth of ground sloths, capybaras, horses, mammoths, and gomphotheres. Semprebon & Rivals (2010) found that the microwear pattern in samples of Hemiauchenia macrocephala from the Irvingtonian of Nebraska is comparable to that of extant mixed feeders, whereas the microwear pattern in samples of Camelops nevadus from the Rancholabrean of Nevada and Camelops sp.…”
mentioning
confidence: 99%
“…These two proposed dietary behaviors indirectly indicates the presence of forested and opened vegetation areas at the Valsequillo Basin during the late Pleistocene. Perez-Crespo et al (2014) have considered a similar scenario at the Valsequillo Basin, based on data derived from the analysis of stable carbon isotopes in the teeth of ground sloths, capybaras, horses, mammoths, and gomphotheres. Semprebon & Rivals (2010) found that the microwear pattern in samples of Hemiauchenia macrocephala from the Irvingtonian of Nebraska is comparable to that of extant mixed feeders, whereas the microwear pattern in samples of Camelops nevadus from the Rancholabrean of Nevada and Camelops sp.…”
mentioning
confidence: 99%
“…However, these remains have not been illustrated. Later, Pérez-Crespo et al (2014, 2019 mentioned the presence of Neochoerus sp. in Valsequillo.…”
Section: The Capybara From Valsequillo Pueblamentioning
confidence: 99%
“…Hydrochoerus hydrochaeris consumes grasses, aquatic plants, and occasionally bark, stems, and leaves (Ojasti, 1973). Recent observations show that H. hydrochaeris has preference for Hymenachne amplexicaulis (an aquatic grass) during the wet season, and feeds on Eleocharis interstincta (a reed) and Paratheria prostrata (a grass) during the dry season (Barreto and Quintana, 2013).…”
Section: Paleoecological Significancementioning
confidence: 99%
“…Los resultados obtenidos por los métodos arriba mencionados demuestran que la mayoría de los ejemplares tenían una dieta mixta basada en plantas C 3 y C 4 , mientras que un menor número de individuos eran estrictamente pacedores con una ingesta exclusiva de plantas C 4 . Lo anterior 604 DISCUSIÓN / CONCLUSIONES se ha documentado en las localidades de El Cedral y Laguna de Las Cruces, en San Luis Potosí (Pérez-Crespo et al, 2009; Tocuila, Estado de México (Pérez-Crespo et al, 2010); Valsequillo, Puebla (Pérez-Crespo et al, 2014); La Cinta-Portalitos y La Piedad-Santa Ana, en el límite Michoacán-Guanajuato (Gutiérrez-Bedolla et al, 2016); El Amate, en la Depresión Central, Chiapas (Pé-rez-Crespo et al, 2015); y ahora en barranca El Morillo y Sierra de Amozoc, Puebla.…”
Section: Edad Y Sexounclassified
“…Este paleoambiente podría ser equiparado al existente durante el Pleistoceno en la Cuenca de Valsequillo, Puebla, zona que se ubica a tan sólo 78 km de barranca El Morillo y a 22 km de Sierra de Amozoc. La reconstrucción del paleoambiente de la Cuenca de Valsequillo indica predominio de vegetación abierta, pero con presencia de coníferas (Pinus, Quercus, Alnus), donde predominaba un clima de baja humedad, que alternaba episodios secos y fríos (Stevens et al, 2012;Pérez-Crespo et al, 2014;Metcalfe et al¸ 2016). Por consiguiente, es posible que este tipo de hábitat fuera común en el centro del estado de Puebla durante el Pleistoceno, favoreciendo el desarrollo de las poblaciones de M. columbi.…”
Section: Preferencia De Hábitatunclassified